Development of an Activity Book as a Learning Medium to Improve Expressive Language Skills in Children with Speech Delay - Tilawati, Nentih; Sukiman (Kirana Publisher (KNPub), 2025)
The purpose of this study was to produce an Activity Book to improve the expressive language of spe.e.ch de.lay children. This study was conducted on children with speech delay with low expressive language skills. The child was not interested in the available media. Teachers at Fitrah Semesta School in building language development still use books with lots of writing that make children with speech delay feel bored. This study uses the R&D method with the ADDIE model to the Development stage by producing an Activity book. In the feasibility test, the researcher used a Likert scale in interpreting based on a questionnaire or instrument made by the researcher. The assessment of the material aspect got a score of 82.2% with a very feasible category, the language aspect 74.5% with a feasible category, and the media aspect 82% with a very feasible category. The response given by students to the activity book media was 90.78% included in the very feasible category.